Comparative analysis of land-based vs. water-based balance training on quality of life and physical and psychological deficits in athletes with chronic ankle instability: a randomized controlled trial - Aynollah Naderi; Khadije Ahi (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Aquatic training is known for its effective and gentle rehabilitation benefits, but its impact on athletes with chronic ankle instability (CAI) remains underexplored. This study compares the effects of water-based and land-based balance training on functional performance, dynamic balance, fear of reinjury, and quality of life in athletes with CAI. Methods Forty-one athletes with chronic ankle instability (CAI) were randomly assigned to water-based (WBBE, n = 21) or land-based (LBBE, n = 20) balance exercise groups, completing 24 sessions of 30–45 min over 8 weeks. Assessments before and after the interventions included functional ankle instability (CAIT), kinesiophobia (TSK-17), quality of life (SF-36), dynamic postural control (Y Balance Test), and functional performance (Figure-8 hop and single-limb side-hop tests). Perceived treatment effects were measured using the Global Rating of Change (GROC) post-intervention. Data were analyzed using mixed-design ANOVA (P ≤ 0.05). Results The statistical analysis of the study revealed no significant time × group interaction effects for CAIT scores, kinesiophobia scores, the Psychological Quality of Life (QoL) Component, or SEBT scores (p > 0.05). The LBBE group showed significant improvements in functional tasks, specifically in F8H and SLSH scores, compared to the WBBE group (p < 0.05), while the WBBE group had better outcomes in overall Quality of Life and the Physical QoL Component than the LBBE group (p < 0.05). Conclusion Both land-based and water-based balance exercises benefit athletes with CAI, with land-based exercises improving functional performance and water-based exercises enhancing physical and overall Quality of Life. A flexible rehabilitation program combining both approaches can optimize recovery, addressing specific needs, even though no significant differences were found in ankle stability, kinesiophobia, psychological Quality of Life, and dynamic balance between the two methods. Trial registration This study was prospectively registered with the University Hospital Medical Information Network Clinical Trial Registry under Clinical Trials UMIN000051746 on July 29, 2023.